The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ijerph17124344
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Stress Disorder among Survivors of the September 11, 2001 World Trade Center Attacks: A Review of the Literature

Abstract: Prior reviews of 9/11-related post-traumatic stress disorder (PTSD) have not focused on the civilian survivors most directly exposed to the attacks. Survivors include those individuals who were occupants of buildings in or near the World Trade Center (WTC) towers, those whose primary residence or workplace was in the vicinity, and persons who were on the street passing through the area. This review reports published information on the prevalence of and risk factors for PTSD, as well as comorbidities associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…However, psychiatric disorders must be analysed in the global context of the pandemic, which has led to significant changes in lifestyle, economy, work, and social relationships. In fact, the high percentage of PTSD is comparable to that described in studies conducted in survivors of wars and catastrophes ( 38 , 39 ).…”
Section: Discussionsupporting
confidence: 74%
“…However, psychiatric disorders must be analysed in the global context of the pandemic, which has led to significant changes in lifestyle, economy, work, and social relationships. In fact, the high percentage of PTSD is comparable to that described in studies conducted in survivors of wars and catastrophes ( 38 , 39 ).…”
Section: Discussionsupporting
confidence: 74%
“…The prevalence of 9/11-related PTSD has varied from 3.8% to 29.6%, depending on populations and time periods [ 1 ]. Previous studies found that exposure to the 9/11 terrorist attack was associated with elevated PTSD levels among a cohort of WTC-exposed adults years after the disaster [ 2 , 3 , 4 ]. While the prevalence of PTSD among WTC survivors has decreased over time, elevated levels of PTSD have persisted for a substantial subgroup.…”
Section: Introductionmentioning
confidence: 99%
“…The long-term health effects of the World Trade Center (WTC) terrorist attacks on September 11, 2001 (9/11) have been acknowledged in recent literature. The frequently studied health outcomes linked to 9/11 include physical health conditions such as asthma, autoimmune diseases, cardiovascular diseases, and cancer, [1][2][3][4][5][6] mental health conditions such as posttraumatic stress disorder (PTSD) and depression, [7][8][9][10] and physical and mental health comorbidities. 11 Many studies have reported significant associations between these health outcomes and 9/11-related dust exposure, [1][2][3][4][5][6] with some studies also noting the temporal associations between mental health problems, particularly 9/11-related PTSD, and physical health outcomes.…”
Section: Introductionmentioning
confidence: 99%